Menilai Potensi Perang dibalik Kepemilikan Nuklir India dan Pakistan - Fajria, Rayhana (Nation State: Journal of International Studies, 2018)
India and Pakistan are two nuclear ownership that flank Kashmir. Claims against Kashmir territory and their history sparked long debate between countries. The conflict became one of the main roots of why India and Pakistan still continue to increase their nuclear power. Conflict continues to heat up creating such an arms race which makes both of them consider the existence of a potential big threat to their sovereignty. In analyzing the issue, this article examine the use of the deterrence theory, where this theory says there are several factors that are important conditions in seeing the possibility of nuclear war. Some of these factors are like; rational state as a condition of the nuclear launch command system, the two countries’ abilities to develop second strike, and the India-Pakistan history of direct involvement in armed conflict.